Vengeance was his: The post-war cinema of Japan's Shohei Imamura. Issue 1 (1st April 2013) - Cardullo, Robert
Outrageous, insightful and sensuous, the films of Shohei Imamura (1926–2006) are among the greatest glories of post-war Japanese cinema, yet Imamura remains largely unknown outside Japan. It is the explosive, at times anarchic quality of Imamura's work that makes him appear 'uncharacteristically Japanese' when seen in the context of the films of Ozu, Mizoguchi or Kurosawa. Perhaps no other film-maker anywhere has so taken up Godard's challenge to end the distinction between 'documentary' and 'fiction' films. Indeed, Imamura has been referred to as the 'cultural anthropologist' of the Japanese cinema. Yet, if anything, Imamura's films argue against an overly clinical approach to understanding Japan, as they often celebrate the irrational and instinctual aspects of Japanese culture. This article is an overview of Imamura's entire career, with emphasis on Vengeance Is Mine (1979), a complex, absorbing study of a cold-blooded killer and Imamura's greatest commercial as well as critical success.